640 Regular bedtime routines and biological obesity risk among 9-year old children from the Fragile Families Child and Wellbeing Study. (3rd May 2021) - Chung, Alicia; Jin, Peng; Moore, Jesse; Nunes, Joao; Seixas, Azizi; Jean-Louis, Giardin
Abstract: Introduction: Obesity rates among Hispanic (26%) and Black (22%) children are considerably higher compared to their white counterparts (14%), which evidence suggests may be attributable to biological, behavioral, and psychosocial factors affecting the family unit. Bio-behavioral factors in the household may affect child health behaviors, including sleep, a known predictor for obesity. Hispanic and Black children report shorter sleep duration, later bedtimes, and are often lacking in bedtime routines, compared to white children. Evidence suggests that early childhood routines are highly predictive of overweight status in children. Herein, we investigate whether bedtime routines are associated with the genetic allele for obesity in a racially diverse sample of children. Methods: Data for the present analysis emanated from wave 5 (Year 9–2007–2010) cohort of the Fragile Families Child and Wellbeing Study dataset. During home visits, interviews with children's mother and father during home visits, around the target child's ninth birthday collected data on home routines and other parent-child relationship and school connectedness topics. Saliva samples were also collected at Year 9 to assess telomere length and DNA methylation levels and changes. The independent variable was regular bedtime routine, and biological variable for fat mass and obesity (rs9939609) was the dependent variable. Adjusted covariates included child's age and BMI, and parent household income. Results: Analysis of the final sample of 466 children showed 52% of the children were male and were 9 years old, on average; 35% were White, 46% Black, 20% Hispanic, 4% Asian and 5% other. The median family income was 42, 500. The child's sleep measures captured was 'children have a regular bedtime routine' was associated with (β = -0.137, p = 0.01) decrease in the odds of having the genetic allele for obesity. Conclusion: Regular bedtime routines among 9-year old Black and Hispanic children may be associated with genetic alleles related to fat mass and obesity. Regular bedtime routines could aid in promoting healthy weight in children. Support (if any): NIH (T32HL129953, K07AG052685, R01MD007716, R01HL142066, K01HL135452, R01HL152453.